Systemic Immune-Inflammation Index Predicts Outcomes in Platinum-Resistant Relapsed Ovarian Cancer - Luxitaa Goenka; Nakka Thejeswar; Biswajit Dubashi; Smita Kayal; Prasanth Ganesan (Indian Journal of Medical and Paediatric Oncology)
We explored the prognostic impact of simple indices that reflect the immunological milieu (neutrophils to lymphocyte ratio [NLR] and systemic immune-inflammation [SII]) in 49 platinum-resistant relapsed ovarian cancer patients. The median progression-free survival (PFS) and overall survival (OS) were 4 and 8 months, respectively. Patients with a lower NLR (≤2.89) had a better PFS (5 vs. 2 months [p = 0.02]) and OS (9 vs. 5 months [p = 0.20]). Factors associated with a worse PFS were NLR > 2.8 (hazard ratio [HR] =2.32, p = 0.02) and SII > 639 (HR =3.70, p = 0.002). SII > 639 independently predicted PFS (HR =4.13, p = 0.03). Future studies should study the validity of inflammatory markers and could consider incorporating it as a biomarker in clinical trials.